2018
DOI: 10.1177/0961000618785408
|View full text |Cite
|
Sign up to set email alerts
|

Correction and retraction practices in library and information science journals

Abstract: Retraction of scholarly publications ensures that unqualified knowledge is purged from the scientific community. However, there appears to be little understanding about how this is practiced among library and information science (LIS) journals. Hence, this study investigated the correction and retraction practices of LIS journals. Journals included in the Web of Science’s information science and library science subject category were selected for the study and the characteristics of the articles corrected or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 48 publications
5
21
0
Order By: Relevance
“…Across different specialties, sizeable numbers of retraction notices do not comply with the guidelines of COPE. [11819] Except one, all the journals evaluated in our study are members of COPE. It is disconcerting that even being a member, a majority of retraction notices failed to comply the guidelines of COPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across different specialties, sizeable numbers of retraction notices do not comply with the guidelines of COPE. [11819] Except one, all the journals evaluated in our study are members of COPE. It is disconcerting that even being a member, a majority of retraction notices failed to comply the guidelines of COPE.…”
Section: Discussionmentioning
confidence: 99%
“…The better a database is in tracking retraction notices, the more easily retracted article can be identified. [19] We observed that search strategy using the name of author and the Publication Type Retraction of Publication failed to retrieve many relevant data. COPE suggests the use of name of author and title of the article in the heading of the retraction notice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborating the results of this study, Brainard (2018), who evaluated retractions between 1997 and 2015, pointed out that most retractions involved scientific fraud (fabrication, falsification, and plagiarism), in addition to false peer review. The study by Ajiferuke and Adekannbi (2020) pointed out that articles in the library and information sciences are withdrawn mainly due to plagiarism, duplication, nonreproducible results, and errors in data. Within anesthesiology, Nair et al (2020) identified that the most common motive for withdrawals was fraud (49.4%), followed by lack of appropriate ethical approval (28%).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, the current situation in relation to retractions has at least four relevant characteristics. First, the retraction rate has increased since the first published retraction in the 1970s (Ajiferuke & Adekannbi, 2020;Brainard, 2018;Fang et al, 2012;Grieneisen & Zhang, 2012;He, 2013;Lei & Zhang, 2018;Resnik, 2015;Tang et al, 2020;Vuong et al, 2020). This growth is linked to the number of journals that began to retract articles, and not necessarily an increase in scientific misconduct (Brainard, 2018;Fanelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%